Wix Web-Based Dance Learning Media to Support Teaching in The Pandemic Era in High School - Sekarningsih, Frahma; Budiman, Agus; Gustiaji, Gaung Rizki (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study intends to develop and design a web for dance learning for high school students. This design-based research focuses on two problems, namely (1) the concept of a dance website design which is expected to be suitable for use as a medium for learning dance in the current pandemic era, and (2) the effectiveness of the dance website that is developed as a digital literacy source that can be used as a medium for learning dance in senior high schools. The research method used in this research is design-based research (DBR) with research stages that include design process, design development, evaluation, and design revision. Data collection techniques were carried out by interview and document study. Data analysis was carried out by combining qualitative and quantitative methods. The results show that the website design developed is relevant to the needs and online-based student learning methods needed during the current Covid-19 pandemic. After going through the validation and testing process, the website design developed can be applied properly. The website developed is easily accessible by students and teachers to support the implementation of dance learning that takes place online. Access mechanisms, material structure, content, and existing supporting features can be used as a means of technology literacy education for students.